'Can You Hear Me Now? 5G Faith in a Pluralistic World' Keynote Adddress - Elnes, Eric (International congregational journal, 2018)
The notion of Christian exclusivism founded in particular interpretation of Jn 14.6 ('I am the way, the truth and the life. No one comes to the Father except through me') is engaged, with a different interpretation offered that is more true to the statement's meaning and opens up new possibilities for bridging the divides between Christianity and other faiths. The claim will be made that it is a 'way of life' that connects us to God, not a particular belief in Jesus, and the 'way of life' Jesus is talking about will be outlined by drawing an analogy to 4G cellular networks. A fifth 'G' will be introduced--which stands for 'Great Awakening that is happening in our own day.